A place out of place: woman and hinterland in Maria Valeria Rezende - Santini, Juliana [UNESP] (Univ Brasilia, Dept Teoria Literaria & Literaturas, 2018)
This work proposes a reflection on displacement of the female character in the novel Outros cantos, by Maria Valeria Rezende. The objective is to problematize how the representation of the hinterland articulates itself, in the narrative, into the composition of a protagonist who, being a woman, narrates her own trip and puts in perspective present and past. What is in question, in this case, is not only the female figure, but also the meanings attributed to hinterland in Brazilian contemporary fiction.
Keywords: hinterland; displacement; female character; Brazilian contemporary narrative